MENGEMBANGKAN KEMAMPUAN MENGAJAR MENGGUNAKAN STRATEGI INSTRUKSIONAL NUMBERED HEADS TOGETHER (NHT) DI KELAS XI IA SMA PGRI 7 BANJARMASIN - Deviana Triwahyu Winarya (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2013)
A study concerning the learning material salt hydrolysis, solubility and solubility product, as well as colloidal IA school in class XI PGRI 7 Banjarmasin. This study aims to develop teaching skills (pedagogy) via reflection, the teacher's role, cognitive and affective learning outcomes of students. Student teacher candidates will experience the transition from student to teacher. The researcher as a student teacher candidates recognize the need to form teacher competence (pedagogical, personal competence, social competence, professional competence) in the final period of the course. The establishment of these competencies do research through Action Research uses instructional strategies Numbered Heads Together (NHT) and improvement through self-reflection, aided by experienced teachers. This research method using action research design with 14 meeting. Each meeting consists of planning, action, observation and evaluation, and reflection. Subjects were high school students of class XI IA PGRI 7 Banjarmasin with the number 34. Data were collected through observation, reflection, questionnaires, and interviews. Data were analyzed with descriptive interpretive techniques. The results showed that the ability to teach researchers had better change based on data from the observer who observed since the beginning of the meeting until the last meeting learning lessons. Transition prospective student teachers become teachers in conducting action research can be used as one way to develop teaching skills. Keywords : NHT models, action research, reflection, salt hydrolysis, solubility and solubility product, colloids.